Penerapan Metode Reverse Engineering and Redesign Dalam Pembuatan Briket Desa Sibalaya Selatan - Mirna Mirna; Andi Herman Jaya; Harnida Wahyuni Adda (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to formulate the Application of Reverse Engineering And Redesign Method in making briquettes from corn cobs in South Sibalaya Village. Based on the results of this study, it shows that briquettes are alternative energy materials that are solid in form containing carbon, have a high calorific value. One of the advantages in developing corn cob briquette products is that it can increase sales by improving existing products or redesigning products, and minimizing shortcomings in order to meet needs, attract attention, and consumer satisfaction. Meanwhile, from the external factor analysis, namely, the development of corn cob briquette products is one of the strategies, in order to maintain or increase its market demand.